Perceptions of the Skills of Graduates in the Library and Information Science and Technology Degree of P. Porto, Portugal: A Statistical Data Analysis of the Alignment Between Students, Teachers, and Employers - Martins, Susana; Lopes, Isabel Cristina; Carvalho, Milena (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – The objective of this research was to identify the four professional competences of graduates in Library and Information Sciences and Technologies (LIST) considered most pertinent, from the points of view of students, teachers, and employers. We also sought to compare the perceptions of the different groups. The study was based on the premise that alignment of these perceptions may enhance the employability of LIST graduates. Methods – A questionnaire, used and validated by Arias-Coello et al. (2014), was further translated by Martins and Carvalho (2018). The questionnaire consisted of a set of questions regarding four dimensions: Information Management; Communication and Interpersonal Relationships; Domain and Application of Information Technologies; Organization Management. We sent the survey by email to the target audience; it was available to complete in April and May 2018. Data analysis included calculating mean and standard deviation, as well as Shapiro Wilk normality tests, statistical tests for multiple comparisons, ANOVA, Kruskal Wallis test, Friedman test, Wilcoxon test, and Pearson's correlation. Results – In relation to certain dimensions, one could think that age would be a determining factor, but this has not been proved. In fact, results showed that age is not a factor that influenced the importance attributed to different competences in the several dimensions. The respondents' academic degrees and areas of knowledge were linked to significant differences transversally. The Kruskal Wallis test indicated that students, teachers, and employers perceived the importance of Information and Communication Technologies (ICT) skills equally. As for the other competences, overall there were significant differences between students and employers, and there were significant differences between students and teachers regarding the perceived importance of organization management skills. There were also significant differences between teachers, students, and employers regarding the perceived importance of communication skills. We also found that responses within the teacher group had less dispersion of answers, therefore there was greater internal agreement. The opposite occurred in the employer group. Conclusion – The differences detected in the perception of the different groups were minor. However, it is necessary to create initiatives for the alignment of the perceptions of students and employers, because if all groups have the same perception, they will develop and value the same skills, responding to the needs of the labor market, thus promoting the employability of LIST graduates. The inclusion of a curricular internship, even one of short duration, in the first year of the degree could also be a way of endeavoring to bring together the expectations of both groups. These suggestions are part of a proposal to change and update the study plan and enhance the performance of course management.